2023
DOI: 10.1111/fare.12896
|View full text |Cite
|
Sign up to set email alerts
|

Changes in familial discussions among East Asian American families during the COVID‐19 pandemic

Abstract: ObjectiveWe examined the degrees of change in familial discussions about racial issues (i.e., race, ethnicity, racism, and discrimination) due to the surge of anti‐Asian discrimination during the COVID‐19 pandemic.BackgroundAsian American family racial–ethnic socialization that teaches the values, information, and perspectives about racial–ethnic group membership and race relations carry great implications for youth development. However, little is known about how anti‐Asian sentiments may have contributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Whether measured in terms of use in the past year or ever while growing up, cultural socialization was more common and more frequent than preparation for bias and promotion of mistrust. Several recent studies document, however, how current events in the last five years, including the COVID‐19 pandemic, anti‐Asian hate crimes, and the national racial reckoning associated with police violence and ensuing protests, have spurred family conversations about ethnicity‐race and in particular, discussions of bias, mistrust, and anti‐racism (Coard et al., 2023; Kim, Zhao, & Toomey, 2023; Lee et al., 2022; Tian, 2023). Coard et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether measured in terms of use in the past year or ever while growing up, cultural socialization was more common and more frequent than preparation for bias and promotion of mistrust. Several recent studies document, however, how current events in the last five years, including the COVID‐19 pandemic, anti‐Asian hate crimes, and the national racial reckoning associated with police violence and ensuing protests, have spurred family conversations about ethnicity‐race and in particular, discussions of bias, mistrust, and anti‐racism (Coard et al., 2023; Kim, Zhao, & Toomey, 2023; Lee et al., 2022; Tian, 2023). Coard et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2022) found that Chinese American youth felt prompted by the BLM movement to respond to anti‐Black messages from parents. Kim, Zhao, and Toomey (2023) found that the most common change due to COVID‐19 in East Asian family conversations about ethnicity‐race was an increase in discussion of racism and discrimination in the United States. Tian (2023) found in their study of Chinese American and Indian American parents that parents saw recent events as a wake‐up call and came to view as necessary for their children's well‐roundedness racial socialization, including lessons about the structural position of Asian Americans in society and the role of collective action to protect and advance the Asian American community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation